2020
DOI: 10.1055/s-0040-1713912
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Body Composition and Pain Intensity in Women with Chronic Pelvic Pain Secondary to Endometriosis

Abstract: Objective To determine the average body composition (percentage of body fat), the anthropometric markers, and the intensity of clinical pain in women with a clinical diagnosis of chronic pelvic pain (CPP) secondary to endometriosis. Methods A case-control study performed with 91 women, 46 of whom with CPP secondary to endometriosis and 45 of whom with CPP secondary to other causes. They underwent an evaluation of the anthropometric parameters by means of the body mass index (BMI), the perimeters (wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Increased risk of coronary heart disease, hypertension, and hypercholesterolemia is also associated with endometriosis . In addition, the pain can negatively affect appetite, affecting BMI and a woman's quality of life Silva et al, 2020). Treating endometriosis pain using NSAIDs can cause side effects such as vomiting and diarrhea, resulting in a decreased tolerance to food .…”
Section: Resultsmentioning
confidence: 99%
“…Increased risk of coronary heart disease, hypertension, and hypercholesterolemia is also associated with endometriosis . In addition, the pain can negatively affect appetite, affecting BMI and a woman's quality of life Silva et al, 2020). Treating endometriosis pain using NSAIDs can cause side effects such as vomiting and diarrhea, resulting in a decreased tolerance to food .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is worth noting that overweight and/or obesity were also reported as influencing factors for pain attenuation in women with endometriosis. This is due to the greater presence of M1 pro-inflammatory macrophages in these individuals [11].…”
Section: Endometriosis and Painmentioning
confidence: 96%
“…An inferior BMI is not only a EMS development risk, but also a predisposing factor for severe endometriosis [21]. Chronic pelvic pain (CPP) is noted for its association with a lower BMI [20][21][22]. A metaanalysis of 11 studies found that a higher BMI coincided with a lower EMS risk.…”
Section: Bmi and Endometriosismentioning
confidence: 99%